PERSEPSI MASYARAKAT TERHADAP KONSERVASI HARIMAU SUMATERA (Panthera tigris sumatrae) DI TAMAN NASIONAL KERINCI SEBLAT (Studi Kasus Desa Pungut Mudik Dan Desa Pungut Hilir) - Adu, Steven Jonathan; Salampessy, Messalina L; Iskandar, Sofian (Jurnal Nusa Sylva, 2019)
Perceptions and community participation in Sumatran tigers (Panthera tigris sumatrae) also influence the success of conservation efforts. For this reason, this study aims to describe the level of public perception of Sumatran tiger conservation efforts. This research uses the case study method. Data was collected using a questionnaire, in-depth interviews and focus group discussions (FGD). Data collection was carried out by means of purposive sampling involving 30 respondents, namely farmers who live and move around the national park. The data collected was analyzed descriptively qualitatively. The results of this study indicate that public knowledge about tigers as animals protected by law has perceptions in the high category (4.03), public knowledge about tiger behavior has a high category (3.93) and public knowledge that tigers currently lack food so often seen in villages that have a very high categorization (4.4). In addition, community knowledge about the ecological benefits of the presenceof Sumatran tigers in the environment has a high category (3.90), public knowledge about the economic benefits of the existence of Sumatran tigers has a high category (3,53). Likewise with public knowledge about the social benefits of the existence of Sumatran tigers have a high category (3.67). The  government and various parties are urgently needed to increase the understanding and active role of the community for Sumatran tiger conservationefforts.